Pengaruh teamwork, semangat kerja, loyalitas kerja terhadap produktivitas karyawan di PT. bank central asia, tbk cabang balikpapan - Aditya Firga Irawan; Sukisno S. Riadi; Siti Maria (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This research was conducted using primary data. Of the 108 employees of PT BANK CENTRAL ASIA Tbk in Balikpapan branch, only 75 permanent employees were taken as samples from this study. The analytical method used is multiple linear regression method, Test Instruments, Hypothesis and Classical Assumption Test. Based on the results of the research showed that Teamwork positive and significant impact on employee productivity seen the t test calculation results for 4,628 with a significance value of 0.000. whereas morale positive and significant effect on the productivity of employees, from the t test calculation for 4,155 with a significance value of 0.000. When working Loyalty positive and significant impact on the productivity of employees, from 2,987 t test calculation with a significance value of 0.004.